Mathematical Model of an Overrunning Mechanism in a New One-Way Clutch - Burgess, S.C.; Stolarski, T.A.; Karp, S. (Engineering Transactions, 1992)
This paper presents a mathematical model of an overrunning mechanism in a new oneway clutch, called a collapsible-band clutch. The operation of the clutch is explained in general terms, and then the governing equations of the mechanism kinematics are derived. The model is used to calculate critical dimensions in the mechanism and to estimate bending stresses that take place during overrunning.